Towards rectifying limitations on species delineation in dusky salamanders (Desmognathus: Plethodontidae): An ecoregion-drainage sampling grid reveals additional cryptic clades - Beamer, David A.; Lamb, Trip (Zootaxa, 2020)
Dusky salamanders (Desmognathus) constitute a large, species-rich group within the family Plethodontidae, and though their systematic relationships have been addressed extensively, most studies have centered on particular species complexes and therefore offer only piecemeal phylogenetic perspective on the genus. Recent work has revealed Desmognathus to be far more clade rich—35 reciprocally monophyletic clades versus 22 recognized species—than previously imagined, results that, in turn, provide impetus for additional survey effort within clades and across geographic areas thus far sparsely sampled. We conceived and implemented a sampling regime combining level IV ecoregions and independent river drainages to yield a geographic grid for comprehensive recovery of all genealogically exclusive clades. We sampled over 550 populations throughout the distribution of Desmognathus in the eastern United States of America and generated mitochondrial DNA sequence data (mtDNA; 1,991 bp) for 536 specimens. A Bayesian phylogenetic reconstruction of the resulting haplotypes revealed forty-five reciprocally monophyletic clades, eleven of which have never been included in a comprehensive phylogenetic reconstruction, and an additional three not represented in any molecular systematic survey. Although general limitations associated with mtDNA data preclude new species delineation, we profile each of the 45 clades and assign names to 10 new clades (following a protocol for previous clade nomenclature). We also redefine several species complexes and erect new informal species complexes. Our dataset, which contains topotypic samples for nearly every currently recognized species and most synonymies, will offer a robust framework for future efforts to delimit species within Desmognathus.